Psychological testing in children with elevated blood lead level: the effect of spirulina - N.I. Hnida; N.H. Lotysh; D.V. Usenko; I.M. Hnidoi; V.N. Kukushkin (Сучасна педіатрія: Україна)
The search for effective and safe remedies to reduce the negative effects of lead on a child’s cognitive sphere is an urgent problem.